2022
DOI: 10.3389/fcell.2022.1030119
|View full text |Cite
|
Sign up to set email alerts
|

The role of serine/threonine phosphatases in human development: Evidence from congenital disorders

Abstract: Reversible protein phosphorylation is a fundamental regulation mechanism in eukaryotic cell and organismal physiology, and in human health and disease. Until recently, and unlike protein kinases, mutations in serine/threonine protein phosphatases (PSP) had not been commonly associated with disorders of human development. Here, we have summarized the current knowledge on congenital diseases caused by mutations, inherited or de novo, in one of 38 human PSP genes, encoding a monomeric phosphatase or a catalytic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…Consequently, non-catalytic subunits may also represent a source of promising disease gene candidates. Indeed, nine genes encoding regulatory subunits of PP1 and PP2A are known to be associated with heritable disorders ( Vaneynde et al, 2022 ). However, systematic analysis of the non-catalytic subunits poses a challenge because of the large number of disparate proteins that interact with PPP catalytic subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, non-catalytic subunits may also represent a source of promising disease gene candidates. Indeed, nine genes encoding regulatory subunits of PP1 and PP2A are known to be associated with heritable disorders ( Vaneynde et al, 2022 ). However, systematic analysis of the non-catalytic subunits poses a challenge because of the large number of disparate proteins that interact with PPP catalytic subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Red amino acids denote metal binding, while blue amino acids denote phosphate binding. The loop switch is indicated in orange [figure adapted from Vaneynde et al (2022 )]. (B) Structure of the catalytic PP2A Cα subunit.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the kinases, there are approximately 200 known phosphatases, the majority of which are tyrosine phosphatases (Sacco et al, 2012). Of the two families of serine/threonine phosphatases, the protein phosphatase-2A family (PP2A) is known to regulate development, apoptosis, transcription, translation, growth and cell division (Moura and Conde, 2019;Vaneynde et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…PP2A enzymes have a heterotrimeric structure consisting of scaffolding (A), catalytic (C) and regulatory (B) subunits. While there are two isoforms each of the A and C subunits, substrate specificity is mediated primarily by the 23 isoforms of the B subunits (Haesen et al, 2014;Vaneynde et al, 2022). PP2A heterotrimers containing the B55α (PR55α) regulatory subunit have been associated with oncogenic signaling (Smits et al, 1992;Hein et al, 2016;Di et al, 2017;Hein et al, 2019), and B55 subunits are found exclusively in forms of PP2A in which the carboxyl terminus of the catalytic subunit (PP2Ac) is methylated at leucine 309 (Longin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%